The Filiation Narrative in the Contemporary French Novel: Jean Rouaud and the Quest for the Absent Master - Dytrt, Petr (Zagadnienia Rodzajów Literackich, 2023)
In this paper two of Rouaud’s texts - L’Invention de l’auteur and La Désincarnation — are mainly being discussed. Our aim is to demonstrate that the story of filiation appears very symptomatic of a new historical situation at the beginning of the twenty-first century, which seems to be written without a “Master” both on the literary and spiritual levels. Thus, there arises the need to accommodate the “ideologies of the end” that appear at the moment when the author enters the literary scene. By trying to establish an impossible dialogue with the Absent, Rouaud voluntarily becomes the archivist of the end of a certain world. We focus on the ways of establishing the link between the search of a father and the observation of the absence of the Father and an attempt to fill in this absence by searchingother literary models.